Hints to discriminate the choice of wet deposition models applied to an accidental radioactive release. (2015) - Quérel, Arnaud; Roustan, Yelva; Quélo, Denis; Benoit, Jean-Pierre
In nuclear emergency management, wet deposition modelling is of crucial importance for correctly evaluating soil contamination after an atmospheric release. Wet deposition is generally divided into two main processes: in-cloud scavenging (rainout) and below-cloud scavenging (washout). The large number of schemes proposed in the literature for both processes reflects the uncertainties in our current understanding of these phenomena. There is presently no scientific consensus to discriminate between the two processes. In order to improve our understanding of the magnitude of modelling uncertainties, a comprehensive sensitivity analysis was performed by focusing on representation of wet deposition fluxes. A large number of model configurations involving different deposition schemes and modelling options were evaluated by comparison with available observations of soil contamination. The objective is to establish a priority rank order of wet deposition schemes for soil contamination modelling.